Meeting Water Quality Goals under Climate Change in Chesapeake Bay Watershed, USA. (22nd October 2018) - Bosch, Darrell J.; Wagena, Moges B.; Ross, Andrew C.; Collick, Amy S.; Easton, Zachary M.
Abstract: Climate change may increase precipitation, temperatures, and pollution loading and necessitate additional measures and costs to achieve water quality goals. We used two climate change models and the mean of the ensemble of seven climate models (Ensemble Mean), a yield prediction model (Soil and Water Assessment Tool‐Variable Source Area), and a farm economic model to estimate how climate change would affect yields and the costs of reducing nitrogen (N) loading in an agricultural subbasin of the Chesapeake Bay. We estimated costs of meeting water quality goals based on the reduction in farm net returns from limits on N loadings under historical and future climate scenarios. Estimated costs of meeting water quality goals increase under future climate for one of the two climate models and for the Ensemble Mean. Major reasons for increased costs are higher predicted N loading from crops and higher N loading reductions to be achieved under future climate. The farm meets N limits by eliminating wheat and reducing corn and soybean production as well as increased use of best management practices (BMPs) including Conservation Reserve Program. Researchers should analyze effects of climate change on the costs of meeting water quality goals using multiple climate change prediction models and considering possible crop substitutions as well as crop and livestock BMPs. Further research should consider how commodity market reactions to producers' choices under climate change affect costs of meeting water quality goals. Abstract : Research Impact Statement : Results from several climate change models show climate change is likely to increase costs of meeting water quality goals in agriculture.